Resource at risk Philippine coral reefs - Rodrigo, Raul ([Manila] Bookmark Video and Moving Images, 1998)
This documentary shows how nearly all of Philippine coral reefs have been damaged by blast, cyanide, and trawley fishing. It shows the effect of this destruction on the people who make their living out of the sea. It also shows how some seaside communities have successfully saved and maintained their coral reefs.
With 1 converted disc.
Narrator, Joonee Gamboa ; Post production director, Joey Conti ; Editors, Nonoy & Bobby Regalado
VHS format.
In English and Filipino with English subtitle.
Keywords: Coral reef ecology -- Philippines; Coral reefs and islands -- Philippines; Coral reef conservation -- Philippines; Environmental sciences